MATCHING OF DRIVE AND VARIATOR CHARACTERISTICS OF GROUND PNEUMATIC CATAPULT - Sereda, Vladislav (Proceedings of National Aviation University (archive), 2015)
The article represents a method of providing a permanent starting overload of pneumatic ground launching device through the modernization of flexible transmission. We show fundamental differences and the main advantages of the investigated polyspast in relation to the cam variator type. Initial and final values of the angle of inclination of the polyspast rope to ensure equal force on the unmanned aerial vehicle in the starting torque and exit from the guide were received. The main gas-thermodynamic and dynamic parameters in the expansion drive machine of catapult were provided.